2014
DOI: 10.3892/or.2014.2971
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-195-5p is a potential diagnostic and therapeutic target for breast cancer

Abstract: MicroRNAs (miRNAs) are a class of highly conserved, small endogenous single-strand non-coding RNAs. They are aberrantly expressed in the circulation and tissue of patients with cancer. Therefore, it has been suggested that they may act as key regulators of carcinogenesis. The aim of the present study was to examine the expression level of miR-195-5p in human breast cancer and its potential role in carcinogenesis. The expression level of miR-195-5p was measured in 40 breast cancer specimens and adjacent normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
63
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 23 publications
4
63
0
Order By: Relevance
“…Consistent with our results, recent studies have shown that miR-195 and miR-497 act as tumor suppressors by inhibiting multiple cell cycle regulators. miR-195 has been shown to directly target CCND1 and CCNE1 in human glioma and breast cancer (Hui et al, 2013;Luo et al, 2014), and both miR-195 and miR-497 have been shown to target CCND1, CCND3, CCNE1, CDC25A and CDK4 in human breast cancer and hepatocellular carcinoma (Furuta et al, 2013;Li et al, 2011). These results indicate that miR-195 and miR-497 can target many cell cycle genes and inhibit cell proliferation in both pathological and physiological conditions.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Consistent with our results, recent studies have shown that miR-195 and miR-497 act as tumor suppressors by inhibiting multiple cell cycle regulators. miR-195 has been shown to directly target CCND1 and CCNE1 in human glioma and breast cancer (Hui et al, 2013;Luo et al, 2014), and both miR-195 and miR-497 have been shown to target CCND1, CCND3, CCNE1, CDC25A and CDK4 in human breast cancer and hepatocellular carcinoma (Furuta et al, 2013;Li et al, 2011). These results indicate that miR-195 and miR-497 can target many cell cycle genes and inhibit cell proliferation in both pathological and physiological conditions.…”
Section: Discussionmentioning
confidence: 68%
“…Consistent with this notion, miR-195 and miR-497 have been shown to be associated with various types of cancers. For example, miR-195 has been shown to act as a tumor suppressor in gastric cancer (Deng et al, 2013), hepatocellular carcinoma (Ding et al, 2013;Xu et al, 2009), bladder cancer (Lin et al, 2012), breast cancer (Luo et al, 2014;Singh and Saini, 2012), leukemia (Diaz-Beya et al, 2012) and other cancer types. miR-497 and miR-195 play similar roles in most physiological processes and miR-497 has also been found to be involved in tumorigenesis (Waters et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…miR-195 has been reported to be downregulated in the tumor tissues and serum of cancer patients. miR-195 is involved in multiple processes during cancer development, including cell proliferation, migration, invasion and metastasis (7)(8)(9)(10)(11)(12). However, the function of miR-195 in cervical cancer development is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Our in vitro experiments demonstrated that miR-195-5p overexpression promoted cell apoptosis and suppressed cell proliferation. Several previous studies revealed reduced miR-195-5p expression in many types of solid cancers, such as gastric, breast, and colon cancers202122. The overexpression of miR-195-5p in these cancers may inhibit cancer cell proliferation, migration and invasion.…”
Section: Discussionmentioning
confidence: 96%